The influence of azaperone treatment at weaning on reproductive function in sows: ovarian activity and endocrine profiles during the weaning-to-ovulation interval. (24th January 2018) - Schwarz, T.; Zięcik, A.; Murawski, M.; Nowicki, J.; Tuz, R.; Baker, B.; Bartlewski, P. M.
Abstract : Azaperone can reduce stress caused by weaning and relocation of breeding sows, but its effects on reproductive processes are still poorly understood. The primary aim of this study was to describe and compare the endocrine and ovarian activity in ultrasonographically monitored second parity sows, with or without azaperone treatment at weaning (2 mg/kg BW i.m.). The intervals from weaning to the onset of estrus and ovulation were both greater ( P <0.05) in azaperone-treated ( n =12) than in control sows ( n =12) by 12 h. Mean daily growth rates of identified antral follicles were less ( P <0.05) in azaperone-treated than in control sows (1.08±0.17 v .1.23±0.18 mm/day; mean±SD) and treated animals exceeded ( P <0.05) controls in the mean ovulation rate (13.7±1.3 v . 12.6±1.2). A transient suppression of cortisol release was observed in the treatment group (at 10 and 30 min after azaperone injections) but circulating cortisol concentrations were variable in both groups of sows for the remainder of the study. The preovulatory rise in LH and estradiol secretion was delayed ( P <0.05), and the duration of the LH surge was greater ( P <0.001) in azaperone-treated sows compared with their control counterparts. The amplitude of episodic fluctuations in serum cortisol concentrations was correlated with the number of stillborn piglets in control sows ( r =0.63, P =0.04). The amplitude and concentration of the preovulatory rise in estradiol secretion were negatively correlated with ovulatory response and litter size ( r =−0.63 to −0.82, P <0.05), whereas the time at which the LH surge ended was directly related to the number of live-born piglets ( r =0.82, P =0.002) in azaperone-treated animals. The present results indicate that administration of azaperone at weaning had a profound effect on preovulatory LH secretion as well as growth kinetics and estrogenicity of ovarian antral follicles. However, the causative associations among various characteristics of the preovulatory LH discharge, ovarian and adrenal steroid secretion post-weaning, and reproductive variables in sows remain equivocal.